PENELUSURAN PERKEMBANGAN KACAPI SUNDA - Asep Nugraha (LP2M ISBI Bandung, 2016)
In the Sundanese society the existence of kacapi has passed through a long period of time and space. This instrument is able to adapt to the social and cultural dynamics ofthe Sundanese society. The instrument has also been well documented by both local and foreign researchers. On one hand, some kacap i are extict because they have been left by their main supporters. On the other hand, some of them are remains, change inshape, and even integrating with other types of art that emerged at thatcertain time. This phenomenon is interesting because it shows theemergence of the various shapes of chordophone (kacapi) in the Snda region. This paper describes the assorted shapes of kacapi by tracing the literatures about kacapi from old times to today.